Behaviour of upstream migrating adult salmon (Salmo salar L.) in the tailrace channels of hydropeaking hydropower plants - Vehanen, Teppo; Louhi, Pauliina; Huusko, Ari; Mäki‐Petäys, Aki; Meer, Olli; Orell, Panu; Huusko, Riina; Jaukkuri, Mikko; Sutela, Tapio
2019